A Platform for Stop‐Flow Gradient Generation to Investigate Chemotaxis. Issue 21 (24th March 2022) - Xiao, Zuyao; Nsamela, Audrey; Garlan, Benjamin; Simmchen, Juliane
Abstract: The ability of artificial microswimmers to respond to external stimuli and the mechanistical details of their origins belong to the most disputed challenges in interdisciplinary science. Therein, the creation of chemical gradients is technically challenging, because they quickly level out due to diffusion. Inspired by pivotal stopped flow experiments in chemical kinetics, we show that microfluidics gradient generation combined with a pressure feedback loop for precisely controlling the stop of the flows, can enable us to study mechanistical details of chemotaxis of artificial Janus micromotors, based on a catalytic reaction. We find that these copper Janus particles display a chemotactic motion along the concentration gradient in both, positive and negative direction and we demonstrate the mechanical reaction of the particles to unbalanced drag forces, explaining this behaviour. Abstract : Janus microswimmers show positive and negative chemotaxis behavior in a microfluidic assay. A flow‐based linear gradient is generated and the flow is stopped during the chemotaxis assay using a retroactive pressure loop.